Fabrication and characterization of centrifugally cast functionally graded A 356-SiCp metal matrix composites. (2021) - Mohan, Arjun; Sajikumar, K.S.
Abstract: Functionally graded materials (FGMs) are inhomogeneous materials which consist of two or more materials. FGM are engineered to have continuously varying spatial composition profile. Vertical centrifugal casting machine is used to cast the A 356 aluminium alloy FGMMC with 5% and 10% percentage by volume SiCp as reinforcing particle. Rotational speed of the machine is kept at 1700 rpm. The size of the SiCp is about 34 μm. The particulate matter is dispersed in the matrix of A 356 which will enhance properties such as hardness, strength and wear resistance through dispersion hardening. Comparison of the density, hardness, ultimate strength, sliding wear and coefficient of friction of FGMMCs were done. The hardness of the composite at the outer region increased about 1.19 times than the base alloy for A 356–5% SiCp FGMMC, 1.35 times for A 356–10% SiCp FGMMC. Ultimate strength observed at the outer periphery are 256 MPa and 263 MPa respectively for 5% and 10% SiCp FGMMCs. Presence of SiCp particles increase the wear resistance and the coefficient of friction. The wear resistance is inversely proportional to sliding velocity and load.